P201 Pneumocystis Jirovecii Prevalence In A Large Uk Adult Cystic Fibrosis Centre. (10th November 2014) - Green, HD; Bright-Thomas, R; Barry, PJ; Horsley, A; Mutton, K; Jones, AM
Abstract : Introduction and objectives: Pneumocystis jirovecii ( PJ ) is an atypical fungus that causes pneumonia in immunocompromised patients. Its role in patients with cystic fibrosis (CF) is unclear. Its reported prevalence in CF ranges from 1–22% but has never been determined in the UK. Here we present preliminary cross-sectional data from an ongoing study at a UK adult CF centre serving >400 patients, to establish prevalence and potential risk factors for infection. Methods: Sputum samples were obtained from 100 randomly selected CF outpatients and sent for routine microbiology and PJ DNA PCR assay at enrolment, subsequent visits, and pulmonary exacerbations requiring intravenous antibiotics within 4 months. Data were recorded for demographics, co-morbidities symptom score, spirometry, inflammatory markers, and prophylactic or recent therapeutic antibiotic therapy. Univariate comparisons were made between sputum PJ positive and negative patients. Chi square tests were used for categorical comparisons and independent sample t-tests for continuous independent variables. Results: Of the 100 patients, 4 of 100 had a positive sputum PJ PCR at baseline. 50 patients had a routine follow up sample between 1 and 4 months: 2 were positive for PJ. 22 patients had a sputum sample analysed at the onset of a pulmonary exacerbation of which 1 was positive for PJ. Hence, a total of 7 of 100 patients had a single positive sample by PCR for PJ. No patient has had >1 positive sample. None of the baseline parameters were significantly different between PJ positive and PJ negative patients at the level p Conclusion: These results suggest that PJ is not an important infecting pathogen in this UK cohort of CF patients. This may be due to frequent use co-trimoxazole for pulmonary exacerbations and high prevalence of prophylactic macrolide antibiotic therapy at our centre compared to other published studies. These preliminary data were underpowered to accurately compare baseline characteristics between PJ positive and PJ negative patients.